The effect of early oral postoperative feeding on the recovery of intestinal motility after gastrointestinal surgery: a systematic review and meta-analysis of randomized clinical trials - Canzan, Federica; Longhini, Jessica; Caliaro, Arianna; Cavada, Maria Luisa; Mezzalira, Elisabetta; Paiella, Salvatore; Ambrosi, Elisa (Frontiers in Nutrition, 2024)
Background & aims: Postoperative ileus is a frequent condition, leading to complications and a longer hospital stay. Few studies have demonstrated the benefit of early oral feeding in preventing ileus after gastrointestinal surgery. This study aims to evaluate the efficacy of early versus delayed oral feeding on the recovery of intestinal motility, length of hospital stay, and complications. Methods: We conducted a systematic review and meta-analysis of randomized control trial, searching PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, and the ClincalTrials.gov up to December 31st, 2022. We evaluated the first passage of the stool, the first flatus, complications, length of postoperative stay, and vomiting. We assessed the risk of bias with the second version of the Cochrane risk of bias tool for randomized trials and the quality of evidence with the Grading of Recommendations Assessment, Development, and Evaluation methodology. Results: We included 34 studies with a median sample size of 102 participants. With a moderate certainty of the evidence, the early oral feeding may reduce the time to the first passage of the stool (MD -0.99 days; CI95% -1.25, -0.72), the first flatus (MD -0.70 days; CI95% -0.87, -0.53), and the risk of complications (RR 0.69; CI95% 0.59-0.80), while with a low certainty of evidence it may reduce length of stay (MD -1.31 days; CI95% -1.59, -1.03). Early feeding likely does not affect vomiting risk (RR 0.90; CI 95% 0.68, 1.18). Conclusions: This review suggests that early oral feeding after gastrointestinal surgery may lead to a faster intestinal recovery, shorter length of postoperative stay, and lower complications. However, a careful interpretation is needed due to the high heterogeneity and the moderate to low quality of evidence. Future studies should focus on the type and starting time of early oral feeding.